2021
DOI: 10.1097/mlr.0000000000001659
|View full text |Cite
|
Sign up to set email alerts
|

Skilled Nursing Facility Participation in a Voluntary Medicare Bundled Payment Program

Abstract: Importance: Model 3 of the Bundled Payments for Care Improvement (BPCI) is an alternative payment model in which an entity takes accountability for the episode costs. It is unclear how BPCI affected the overall skilled nursing facility (SNF) financial performance and the differences between facilities with differing racial/ethnic and socioeconomic status (SES) composition of the residents.Objective: The objective of this study was to determine associations between BPCI participation and SNF finances and across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Following previous research (Li et al, 2015), we linked the participation information to the Nursing Home Compare (NHC) reports to identify all the 16,678 Medicare-certified SNFs nationally and their participation status. Since hospital-based SNFs are different from free-standing SNFs in terms of resident severity, care practice, and cost accounting system (Li et al, 2015; Ying et al, 2022), we excluded the 1176 hospital-based SNFs from the dataset. According to previous research (Harrington et al, 2007; Harrington et al, 2012; Li et al, 2015), 1080 free-standing SNFs were excluded from the remaining group as they had zero or more than twenty-four staffing hours, or their staffing hours were outside three standard deviations of the national mean.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following previous research (Li et al, 2015), we linked the participation information to the Nursing Home Compare (NHC) reports to identify all the 16,678 Medicare-certified SNFs nationally and their participation status. Since hospital-based SNFs are different from free-standing SNFs in terms of resident severity, care practice, and cost accounting system (Li et al, 2015; Ying et al, 2022), we excluded the 1176 hospital-based SNFs from the dataset. According to previous research (Harrington et al, 2007; Harrington et al, 2012; Li et al, 2015), 1080 free-standing SNFs were excluded from the remaining group as they had zero or more than twenty-four staffing hours, or their staffing hours were outside three standard deviations of the national mean.…”
Section: Methodsmentioning
confidence: 99%
“…Another key independent variable is a BPCI exposure variable, defined as the proportion of months the SNF was exposed to the program in a given year as SNFs could join BPCI on a rolling base that resulted in different BPCI enrollment dates across years. Similar to the method used in previous studies (Ryan et al, 2017; Ying et al, 2022), this variable is a continuous variable and has a value of 0–1 to fully capture the extent to which the SNF exposed to BPCI in each year. For example, if a persistent-enrollment SNF joined BPCI on October 1, 2013, the exposure variable was specified as 0 for 2010 to 2012, 3 of 12 = .25 in 2013, and 1 for 2014 to 2017.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 SNFs, which comprised 89% of all model 3 participants, 6 are likely to respond to the reimbursement change as the operation of the facility heavily depends on Medicare payments. Recent national studies [7][8][9][10] have evaluated the associations between SNF participation in BPCI model 3 and changes in efficiency and quality of PAC. For example, Barnett et al 7 found that model 3 was significantly associated with reduced institutional spending among Medicare beneficiaries undergoing lower extremity joint replacement (LEJR) from 2013 to 2017, which was largely attributed to decreases in SNF length of stay without changes in readmissions.…”
mentioning
confidence: 99%